Lactic acid in the vaginal milieu modulates the Candida-host interaction - Diletta Rosati; Marisa Valentine; Mariolina Bruno; Arnab Pradhan; Axel Dietschmann; Martin Jaeger; Ian Leaves; Frank L. van de Veerdonk; Leo A.B. Joosten; Sumita Roy; Mark H. T. Stappers; Neil A.R. Gow; et al. (Virulence)
Vulvovaginal candidiasis (VVC) is one of the most common infections caused by Candida albicans. VVC is characterized by an inadequate hyperinflammatory response and clinical symptoms associated with Candida colonization of the vaginal mucosa. Compared to other host niches in which C. albicans can cause infection, the vaginal environment is extremely rich in lactic acid that is produced by the vaginal microbiota. We examined how lactic acid abundance in the vaginal niche impacts the interaction between C. albicans and the human immune system using an in vitro culture in vaginal simulative medium (VSM). The presence of lactic acid in VSM (VSM+LA) increased C. albicans proliferation, hyphal length, and its ability to cause damage during subsequent infection of vaginal epithelial cells. The cell wall of C. albicans cells grown in VSM+LA displayed a robust mannan fibrillar structure, β-glucan exposure, and low chitin content. These cell wall changes were associated with altered immune responses and an increased ability of the fungus to induce trained immunity. Neutrophils were compromised in clearing C. albicans grown in VSM+LA conditions, despite mounting stronger oxidative responses. Collectively, we found that fungal adaptation to lactic acid in a vaginal simulative context increases its immunogenicity favouring a pro-inflammatory state. This potentially contributes to the immune response dysregulation and neutrophil recruitment observed during recurrent VVC.